Distribution of commensal rodents in rain-fed and irrigated areas of Swat district, Khyber Pakhtunkhwa, Pakistan - Khan,W. (2022)
Abstract Distribution pattern and relative abundance of the agricultural rodent pests of rain-fed and irrigated areas of district Swat Khyber Pakhtunkhwa, Pakistan were recorded from April 2011 to November 2013 using wire mesh live traps. A total of 350 rodents (269 Rattus rattus and 81 Mus musculus) were captured under 2268 trap nights (trap success: 0.15). Regression of daily captures on cumulative captures revealed an estimate of 350 rodents from all the sampled structures with an average of 21.8 rodents per crop field. House rats (R. rattus; 76.8% of captures) were numerically dominant in almost all types of agricultural fields, and were significantly different from the mice (Mus musculus; 23.1% of captures). Both species were found together in some fields. The sex ratio revealed that males outnumbered the females in both of the reported species.